Modulation of nickel toxicity by glycinebetaine and aspirin in Pennisetum typhoideum - Xalxo, Roseline; Yadu, Bhumika; Chakraborty, Piu; Chandrakar, Vibhuti; Keshavkant, Sahu (Acta Biologica Szegediensis, 2017)
Germinated Pennisetum typhoideum seeds were grown under phytotoxic amount of nickel (Ni) and its combinations with aspirin (Asp) and/or glycinebetaine (GB). The results revealed that exposure to Ni caused reduced growth and membrane stability index of P. typhoideum, which were correlated with the accumulated Ni and reactive oxygen species. Oxidative stress markers; malondialdehyde, 4-hydroxy-2-nonenal and lipoxygenase were also elevated by Ni, while were diminished significantly by exogenously applied Asp and/or GB. However, considerable loss in protein and DNA contents were discernible in Ni subjected tissues, but were stimulated largely in the Asp and/or GB applied radicles. Additionally, alteration in the activities and native-PAGE profiles of antioxidant enzymes (superoxide dismutase, catalase, guaiacol peroxidase and ascorbate peroxidase) were discernible in response to Ni, which are reputed to counterbalance the oxidative condition. However, exogenous addition of Asp and/or GB activated the defense system and uplifted proline accumulation in stressed P. typhoideum. The results approved that combined addition of Asp and GB performed far better in Ni-stress mitigation than their alone application. Conducted study indicated that combined application of Asp and GB served as complementary tool to confer tolerance by up-regulating the antioxidant enzymes and thus can be implicated in the mitigation of Ni-toxicity.